Media Sosial Meningkatkan Kinerja Pemasaran Produk Usaha Mikro: Sebuah Studi dari Kota Pekanbaru - Eka Setiyaningsih; Makhdalena; Brilliant Asmit (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
The aim of carrying out this research is to explain how social media is used in marketing micro business products and to find out whether social media has an impact on the development of micro businesses. This research uses this type of qualitative descriptive research using a phenomenological approach. The phenomenological method seeks to understand the meaning of events and their relationship to people in certain situations. Based on the results of research on the use of social media in marketing MSME products, Simpang Baru Village, Pekanbaru City, Riau Province, it can be seen that micro businesses in Simpang Baru Village use Instagram and WhatsApp social media in marketing or promoting their products. They use social media by uploading photos and videos by editing them through the application and then uploading them with words that attract customers. Apart from that, micro businesses also rent or utilize well-known social media accounts to promote products and goods so that their products are known to many people. However, from the use of social media, the language used is not good and correct and in terms of business premises there are still many buyers who do not get a seat. The existence of social media has a positive impact on micro businesses to expand product marketing. The existence of social media provides convenience and good benefits for increasing customers and also increasing income. However, when using social media you must also be consistent so that your business becomes better known and grows. If it is not consistent, what will happen is a decrease in income.